Anlageberatung Das System der zivilrechtlichen Haftung von Kreditinstituten - Krimphove, Dieter

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Complexity results for the default- and autoepistemic logic - Steffen, Eckhard (Computer Science Logic)

Experimental Results to Interprocessor Communication in Distributed Transputer-Systems - Ginthör, Robert; Platzner, Marco; Weiss, Reinhold (Proceedings of the 1st Austrian-Hungarian Workshop on Transputer Applications)

Contribution to the AC-analysis of resonant converters; analysis of the series-parallel resonant converter including effects of parasitics and lossless snubbers for optimized design - Fröhleke, Norbert; Kunze, Jürgen; Fiedler, A.; Grotstollen, Horst (APEC '92 Seventh Annual Applied Power Electronics Conference and Exposition)

Resonant power supply for barrier discharge UV-excimer sources - Kunze, Jürgen; Fröhleke, Norbert; Grotstollen, Horst; Margaritis, Basile; Locken, F. (Conference Record of the 1992 IEEE Industry Applications Society Annual Meeting)

Hilbert, Zermelo und die Institutionalisierung der mathematischen Logik in Deutschland - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)
Rezensionen: MR 93d:01046 (Charles F. Kielkopf); Zbl. Math. 756.01034 (I. Grattan-Guinness).

Wozu Algebra der Logik? Zum Lebenswerk von Ernst Schröder [Abstract] - Peckhaus, Volker (III. Österreichisches Symposion zur Geschichte der Mathematik. Neuhofen an der Ybbs, 8. bis 14. November 1992. Umwege, Abschneider und Sackgassen ... über Abweichungen vom „normalen“ Gang der Entwicklung. Kurzfassungen der Vorträge)

Arithmetik — Logik — absolute Algebra. E. Schröders Suche nach einer universalen Theorie der Verknüpfungen [Abstract] - Peckhaus, Volker (Deutsche Mathematiker-Vereinigung. Jahrestagung 13.–18.9.1992 in Berlin. Vortragsauszüge)

Topologien und Schalterkonzepte für Schaltnetzteile hoher Leistung bei geringer Ausgangsspannung - Fröhleke, Norbert

Pulswechselrichtergespeiste Drehstromantriebe unter Berücksichtigung des Stromlückens - Wang, Yongfan

The Pseudoexhaustive Test of Sequential Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems (TCAD))

Generation of Vector Patterns through Reseeding of Multiple-Polynomial Linear Feedback Shift Registers - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard (IEEE International Test Conference (ITC'92))

Die Aktualgenese von Raummodellen und ihr Einfluß auf die Linearisierung - Buhl, Engelbert; Buhl, Heike M.

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)

The EXPRESS Information Modeling Workbench - A New Approach to Graphical Design Environments - Müller, Wolfgang; Kleinjohann, Bernd (Proceedings of the 2nd EXPRESS User's Group Conference)

DIRECT MODULATION 565 MBIT/S OPTICAL PSK HETERODYNE SYSTEM WITH SOLITARY SL-QW-DFB LASERS USING NOVEL SUPPRESSION OF PHASE-TRANSITION PERIODS IN CARRIER RECOVERY - MEISSNER, E; Noé, Reinhold; BORCHERT, B; RODLER, H (ELECTRONICS LETTERS)

FULLY ENGINEERED COHERENT MULTICHANNEL TRANSMITTERS AND RECEIVERS WITH LOW-COST POTENTIAL - Noé, Reinhold; RODLER, H; EBBERG, A; MEISSNER, E; BODLAJ, V; DROGEMULLER, K; WITTMANN, J (ELECTRONICS LETTERS)

ACCURATE AND SIMPLE OPTICAL FREQUENCY STABILIZATION FOR A COHERENT MULTICHANNEL SYSTEM - Noé, Reinhold; DROGEMULLER, K (IEEE PHOTONICS TECHNOLOGY LETTERS)

Chromaticity of polymer-dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Heppke, G. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Behaviour of polymer dispersed cholesteric droplets with negative dielectric anisotropy in electric fields - Kitzerow, Heinz-Siegfried; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Microscopic observations of axial and radial nematic droplets for a dual-frequency addressable liquid crystal - Kitzerow, Heinz-Siegfried; Xu, F.; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

DIRECT MODULATION 565 MB/S DPSK EXPERIMENT WITH 62.3 DB LOSS SPAN AND ENDLESS POLARIZATION CONTROL - Noé, Reinhold; MEISSNER, E; BORCHERT, B; RODLER, H (IEEE PHOTONICS TECHNOLOGY LETTERS)

Electrostriction dynamics of blue phase II crystallites - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Rand, J.; Xu, J.; Heppke, G. (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Dynamic response of a blue phase to an applied field - Dolganov, V. K.; Heppke, G.; Kitzerow, Heinz-Siegfried (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Dynamics of polymer-dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Rand, J.; Crooker, P. P. (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Electric-field effects on nematic droplets with negative dielectric anisotropy - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Linear electro‐optic effects in polymer‐dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Helical unwinding in polymer-dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Antiferroelectric Switching in Polymer-Dispersed Liquid Crystals - Molsen, Henning; Kitzerow, Heinz-Siegfried; Heppke, Gerd (Japanese Journal of Applied Physics)
We investigated the switching behavior of the well-known antiferroelectric liquid crystal (R)-4-(1-methylheptyloxycarbonyl)phenyl-4'-octyloxybiphenyl-4-carboxylate (MHPOBC), embedded in a polymer matrix. The alignment of the liquid crystal in the UV-cured adhesive was controlled by mechanical shear during the polymerization-induced phase separation. Multistable switching with time constants down to 150 µs indicates that antiferroelectric PDLC devices are promissing for electrooptic application as flexible displays.
Keywords: General Physics and Astronomy; General Engineering

Deformed-Helix Ferroelectric Effect in Polymer-Dispersed Ferroelectric Liquid Crystals - Molsen, H.; Kitzerow, Heinz-Siegfried; Heppke, G. (SID Digest of Technical Papers)

Blue Phases - Crooker, P. P.; Kitzerow, Heinz-Siegfried (Condensed Matter News)

Dissipative Dynamics of an Electronic Wavepacket in a Semiconductor Double Well Potential - Meier, Torsten; Leo, K.; Shah, J.; Damen, T.C.; Schulze, A.; Schmitt-Rink, S.; Thomas, P.; Göbel, E.O.; Chuang, S.L.; Luo, M.S.C.; Schäfer, W.; Köhler, K.; et al. (IEEE journal of quantum electronics)
The authors present a detailed study of coherent tunneling oscillations of an optically excited electronic wavepacket in a semiconductor double quantum-well structure. The oscillation of the wavepacket between the two wells is traced by time-resolved pump-probe spectroscopy as well as time-resolved degenerate four-wave mixing. The experimental observations are compared with a simple theoretical model. The motion of the wave packet is studied as a function of both an external electric field and the lattice temperature. While the oscillation frequency shows the expected dependence on electric field, it increases with temperature at fixed electric field when perfectly delocalized electronic states exist at low temperature.

Optical investigation of Bloch oscillations in a semiconductor superlattice - Meier, Torsten; Feldmann, J.; Leo, K.; Shah, J.; Miller, D.A.B.; Cunningham, J.E.; von Plessen, G.; Schulze, A.; Thomas, P.; Schmitt-Rink, S. (Physical Review B)
We report the study of optical dephazing of Wannier-Stark ladder excitations in a semiconductor superlattice by means of transient degenerate four-wave mixing. We observe pronounced modulations of the signal with a time period varying linearly with the electric field. The time period is found to equal the temporal periodicity of Bloch oscillations, in agreement with theory. In addition, we find that the dephazing time decreases with increasing localization of the Wannier-Stark states, which is attributed to carrier escape out of the lowest miniband.

Time Resolved Four Wave Mixing in GaAs/AlAs Quantum Well Structures - Meier, Torsten; Göbel, E.O.; Koch, M.; Feldmann, J.; von Plessen, G.; Schulze, A.; Thomas, P.; Schmitt-Rink, S.; Köhler, K.; Ploog, K. (physica status solidi (b))
Femtosecond nonlinear laser spectroscopy is applied to study the dynamics of coherent optical excitations in semiconductors. In particular, excitonic excitations in quantum wells and superlattice structures are considered. Two examples demonstrate that four-wave mixing experiments with time-resolved detection of the nonlinear signal are able to distinguish between quantum beats and polarization interference.v

A Silicon Technology for Monolithic Integration of Optical Waveguides, Photodetectors and VLSI CMOS Circuits - Hilleringmann, Ulrich; Adams, S; Goser, K (Proceedings ISSSE’92)

Electrooptical coupling of waveguides and VLSI circuits integrated on one silicon chip - Adams, S; Hilleringmann, Ulrich; Goser, K (EFOC LAN)

Michel plays Petrucciani. Oder: "So wenig sind wir auf uns selbst gestellt." Oder: Praktisch-theologische Wahr-Nehmungen in dem "Spielraum von Schnitten" - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

THz-emission from photoexcited semiconductor superlattices with applied ac and dc electric fields - Meier, Torsten; Thomas, P.; Koch, S.W. (Technical Digest. Summaries of Papers Presented at the Quantum Electronics and Laser Science Conference)
Summary form only given. The numerical investigations are based on a microscopic many-body theory which allows one to compute the linear and nonlinear optical properties of semiconductor superlattices in the presence of homogeneous electric fields applied in the growth direction. The THz-emission due to the field-driven dynamics of photoexcited carriers is investigated for the combined action of static and alternating fields. For a driving field it was shown within a simple model that the equations governing the intraband dynamics in the field-driven superlattice should be analogous to the ones describing the superconducting Josephson junction. The transport properties in this regime can be described by the picture of multi-photon-assisted tunneling between Wannier-Stark states.

Distribution of exciton binding-energies in disordered semiconductor quantum-wells - Meier, Torsten; Euteneuer, A.; Finger, E.; Hofmann, M.; Stolz, W.; Thomas, P.; Koch, S.W.; Ruhle, W.W. (Technical Digest. Summaries of Papers Presented at the Quantum Electronics and Laser Science Conference)
Summary form only given. Partly non-degenerate four-wave mixing is able to detect coherent coupling between excitonic resonances like e.g. light-hole and heavy-hole excitons or between an exciton and its continuum states. We apply an extension of this method, which we call selective coherent spectroscopy (SCS), to symmetrically strained (GaIn)As/Ga(PAs) multiple quantum-wells. The samples are excited simultaneously by a picosecond pulse with wavevector k/sub 1/ and a 100 fs pulse with wavevector k/sub 2/. The central wavelength of the picosecond pulse is scanned over the entire spectrum of the 100 fs pulse and the four-wave mixing signal in the direction 2k/sub 2/-k/sub 1/ is detected at a fixed energy. This scan provides an SCS spectrum.

Influence of carrier-correlations on the optical Stark effect of semiconductors - Meier, Torsten; Sieh, C.; Koch, S.W.; Brick, P.; Hubner, M.; Ell, C.; Prineas, J.; Khitrova, G.; Gibbs, H.M. (Technical Digest. Summaries of Papers Presented at the Quantum Electronics and Laser Science Conference)
Summary form only given. For a proper understanding of nonlinear optical experiments in semiconductors even the low-density limit Coulomb-induced many body correlations beyond the Hartree-Fock decoupling scheme need to be considered. In the coherent X(3) limit these correlations manifest themselves in the contributions of bound and unbound two-exciton states to the optical response. The understanding of nonlinear excitonic effects in the Stark effect of semiconductors including carrier-correlations is still of fundamental interest.

Terahertz Electromagnetic Pulse Generation and Four-Wave Mixing in Coupled Quantum Wells - Meier, Torsten; Schulze, A.; Scmittrink, S.; Thomas, P.; Chuang, S.L. (International Quantum Electronics Conference)
Recent experiments by Roskos et al. in ultrashort optical pulse excitation of biased coupled quantum wells have shown remarkable generation of terahertz electromagnetic radiation. Two different effects were identified: (i) an oscillatory field of frequency corresponding to the separation between the coupled levels in the quantum-well pair (~ 1.5 THz); and (ii) an “instantaneous” electromagnetic field pulse that appears to follow the time evolution of the exciting laser pulse. The oscillatory field is understood to be caused by the coherent oscillation of optically created electrons from one well to the other.[1] The “instantaneous” part we believe is caused by a new mechanism proposed in Ref. 2. The essence of this “instantaneous” mechanism is that electron-hole pairs are created in a biased semiconductor with a net polarization. The density of these pairs follows the light field, as does the induced polarization, hence, generating an electromagnetic source that follows the light pulse. Such mechanisms have been discussed before for photon energies below the optical bandgap energy,[3] although they have so far been difficult to observe. In our work, we have generalized and extended such effects to photon energies above the handgap energy. In this paper we will discuss both of these mechanisms as well as the fourwave-mixing (FWM) signal,[4] and show how they can be understood within one unified formalism. We will also show that the calculations agree well with the experimental results.

On the Observability of Bloch Oscillations in Time-Resolved Four-Wave-Mixing - Meier, Torsten; von Plessen, G.; Schulze, A.; Thomas, P. (International Quantum Electronics Conference)
In the presence of a homogeneous electric field, 𝐹→, each Bloch state in a crystal changes quasimomentum according to the so-called acceleration theorem Thus, in the absence of interband tunneling and scattering processes, each Bloch state moves at a constant velocity in k-space and executes a periodic motion in the reduced zone scheme by undergoing a Bragg reflection between each two traversals of the Brillouin zone.

Entwurf einer Benutzeroberfläche für die Analyse von kontextfreien und DCG - Grammatiken und ihre didaktische Verwendung. Erste Staatsarbeit im Fach Informatik - Herzig, Bardo

Physics Education in East and West Germany - Jonas-Ahrend, Gabriela

„Wie wird künftig Meusel die hungrige Nachwelt hetzen und peinigen“. Deutsche Romane 1815-1830 in der Fürstlichen Bibliothek Corvey. Vorläufiges zum Forschungsprojekt „Der deutsche Roman 1815-1830" - Eke, Norbert Otto (Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn)

Diskussionsberichte zu den Sektionen 2 („Roman“) und 3 („Dramen“) sowie der Abschlußdiskussion des 1. Internationalen Corvey-Symposions - Eke, Norbert Otto (Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn)
Angaben zur Herausgeberschaft: Hg. von Rainer Schöwerling und Hartmut Steinecke unter Mitarbeit von Norbert Otto Eke und Günter Tiggesbäumker

Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn
Präzisierung der Herausgeberschaft: Hg. von Rainer Schöwerling und Hartmut Steinecke unter Mitarbeit von Norbert Otto Eke und Günter Tiggesbäumker

Fomenko, A.T. Symplectic Geometry (Gordon and Breach, 1988) - Hilgert, Joachim (JBer. DMV)